Ceria-Catalysed Production of Dimethyl Carbonate from Methanol and CO2: Effect of Using a Dehydrating Agent Combined with a Solid Cocatalyst - Dichao Shi; Svetlana Heyte; Mickaël Capron; Sébastien Paul (Molecules)
The direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol over ceria-based catalysts, in the presence of a dehydrating agent shifting the thermodynamical equilibrium of the reaction, has received significant interest recently. In this work, several dehydrating agents, such as molecular sieves, 2,2-dimethoxypropane (DMP), dimethoxymethane (DMM) and 1,1,1-trimethoxymethane (TMM), are combined with commercial ceria to compare their influence on the DMC yield obtained under the same set of operating conditions. TMM is found to be the most efficient; however, its conversion is not complete even after 48 h of reaction. Therefore, it is proposed for the very first time, to the best of our knowledge, to add a second solid cocatalyst in the reaction medium to accelerate the TMM hydration reaction without degrading the DMC already formed. Basic oxides and acidic zeolites with different Si/Al ratios are employed to accelerate the hydration of TMM, so as to improve the DMC yield. 13X was identified as the best option to play this role. Finally, three different commercial cerias are tested in the presence of TMM and molecular sieve 13X as the second catalyst. The most efficient combination of ceria, TMM, and molecular sieve 13X is ultimately tested in a 250 mL autoclave to start to scale up the process. A very high DMC production of 199.5 mmol DMC/gcat. is obtained.